Liquid to particle heat transfer in fluidised beds - Hassan, Onn; Stepanex, J.B. (1989)
The liquid to particle heat transfer coefficient was measured in beds fluidized by water and three glycerol-water mixtures. A literature survey revealed little agreement between the results of previous investigators of fluid to particle heat transfer. A variety of techniques was employed to measure the fluid to particle heat transfer coefficient, also, temperature data were recorded and interpreted in many ways. In this investigation, the liquid to particle heat transfer coefficients were measured under unsteady state conditions by introducing a step change in the temperature of the inflowing liquid to beds of aluminium and alumina particles fluidised by water or three glycerol-water mixtures. The coefficients were measured by employing the technique of tagging a particle with a thermocouple which allows a direct measurement of particle temperature.